2020
DOI: 10.1128/jcm.01677-19
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Bedaquiline Phenotypic Drug Susceptibility Testing Methods and Breakpoints: a Multilaboratory, Multicountry Study

Abstract: Drug-resistant tuberculosis persists as a major public health concern. Alongside efficacious treatments, validated and standardized drug susceptibility testing (DST) is required to improve patient care. This multicountry, multilaboratory external quality assessment (EQA) study aimed to validate the sensitivity, specificity, and reproducibility of provisional bedaquiline MIC breakpoints and World Health Organization interim critical concentrations (CCs) for categorizing clinical Mycobacterium tuberculosis isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…The ECOFFs determined in this study for both the frozen and dry BMDs matched those in the Ismail et al study based on ECOFFs of 95, 97.5, and 99% (17). Although the ECOFF 99% is preferred, the Kaniga et al study showed that using a well-characterized EQA panel, the ECOFF of 0.12 g/ml based upon 97.5% was the most robust concentration to clearly delineate wild-type from non-wild-type populations (22). In the present study, applying this cutoff yielded good overall performance for correctly classifying susceptibility.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The ECOFFs determined in this study for both the frozen and dry BMDs matched those in the Ismail et al study based on ECOFFs of 95, 97.5, and 99% (17). Although the ECOFF 99% is preferred, the Kaniga et al study showed that using a well-characterized EQA panel, the ECOFF of 0.12 g/ml based upon 97.5% was the most robust concentration to clearly delineate wild-type from non-wild-type populations (22). In the present study, applying this cutoff yielded good overall performance for correctly classifying susceptibility.…”
Section: Discussionsupporting
confidence: 68%
“…The WHO-proposed CC was based on multiple studies that lacked standardization and did not include BMD. An external quality assessment (EQA) study by Kaniga et al confirmed the appropriateness of the susceptible interpretive criterion by Ismail et al and WHO interim CCs using a set of well-characterized isolates (22).…”
mentioning
confidence: 77%
“…The minimum inhibitory concentration (MIC) of bedaquiline (Biochempartner, China) for all MTB isolates was determined by microplate alamarBlue assay using two-fold dilutions ranging from 0.008 mg/mL to 4 mg/mL, as described previously (Kaniga et al, 2020;Pang et al, 2017). Briefly, bacterial clones were harvested from the surface of LJ slants.…”
Section: Minimum Inhibitory Concentrationmentioning
confidence: 99%
“…The detection of resistance to BDQ and DLM is critical to ensuring effective treatment and care for DR-TB patients and preventing ongoing transmission. Although evidence for the validation and standardization of efficient methods for MICs and the setting of breakpoints for BDQ and DLM continues to expand ( 22, 34, 50, 51 ), there is still a notable lack of suitable data on resistance-related genomic variants ( 52 ). Moreover, phenotypic methods are too slow to provide early indication of susceptibility status at the time of treatment initiation.…”
Section: Discussionmentioning
confidence: 99%